2006
DOI: 10.3168/jds.s0022-0302(06)72411-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Use of Imported Nitrogen, Phosphorus, and Potassium and Potential for Reducing Phosphorus Imports on Idaho Dairy Farms

Abstract: Eight commercial dairies from south central Idaho were surveyed to estimate the whole-farm surpluses of N, P, and K and to investigate the possibility of reducing P excretions through dietary manipulation. Nitrogen, P, and K imports and exports were monitored in a 12-mo period, and samples from the diets, feeds, feces, urine, and manure were collected at regular farm visits. Soils from manure-amended fields were sampled in the spring and fall. In all cases, the largest import of N, P, and K to the dairy was wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
69
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 30 publications
20
69
3
5
Order By: Relevance
“…For example, a large study involving 130 commercial dairy systems across Western Europe reported average regional N surpluses between 93 and 502 kg N/ha, 15 and 28 g N/L and N-use efficiencies ranging between 19 and 40% (Raison et al 2006). Similar ranges in N surpluses and use efficiencies have been reported on commercial dairy farms in New Zealand (Ledgard et al 2004), the USA (Hristov et al 2006), and Europe (i.e. Van der Meer 2001;Nevens et al 2006;Fangueiro et al 2008;Treacy et al 2008).…”
Section: Nutrient Balances and Use Efficienciessupporting
confidence: 49%
“…For example, a large study involving 130 commercial dairy systems across Western Europe reported average regional N surpluses between 93 and 502 kg N/ha, 15 and 28 g N/L and N-use efficiencies ranging between 19 and 40% (Raison et al 2006). Similar ranges in N surpluses and use efficiencies have been reported on commercial dairy farms in New Zealand (Ledgard et al 2004), the USA (Hristov et al 2006), and Europe (i.e. Van der Meer 2001;Nevens et al 2006;Fangueiro et al 2008;Treacy et al 2008).…”
Section: Nutrient Balances and Use Efficienciessupporting
confidence: 49%
“…En promedio, las once fincas importaron 4636 (±3491) kg de nitrógeno donde un 75% provenía de alimentos y solamente un 25% era proveniente de fertilizantes. Otros estudios han demostrado también que la variable que aporta la mayor cantidad de N es por el ingreso de alimentos al sistema (Spears et al, 2003;Hristov et al, 2006). Sin embargo, en el estudio de Hristov et al (2006), la proporción de N importado a través de alimentos fue del 90%.…”
Section: Entrada De Nitrógenounclassified
“…La fijación de N por medio de leguminosas podría hacer un importante aporte, pero ninguna de las fincas estudiadas contaban con leguminosas en los potreros. Otros estudios han reportado que el aporte de N por medio de leguminosas puede llegar a ser el segundo en importancia (Hristov et al, 2006). La importación de N a través de la compra de animales fue pr�cticamente nula, especialmente cuando se observó que la mayoría de explotaciones no compraron ningún tipo de animal durante la duración del estudio.…”
Section: Entrada De Nitrógenounclassified
See 2 more Smart Citations